2019
DOI: 10.1002/anie.201813589
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Calixarene Scaffolds for NO Detection in Protic Media

Abstract: We present the first fluorescent water‐soluble conjugated calixarene scaffolds that are capable of NO gas detection. Two different scaffolds, one based on a 5,5′‐bicalixarene structure and its isomer bearing two distantly conjugated calixarene moieties, were synthesized. While the fluorescence of both isomers is quenched upon either passing of NO gas or generating it in situ from diethylamine NONOate, the bicalixarene‐based scaffold showed a significantly stronger response. We also present an example of a dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“… 8 , 9 Considering the importance of nitric oxide in a variety of biological processes, 10 we developed the fluorescent oxygen-depleted 5,5′-bicalixarene scaffolds 11 for reversible NO detection in solution. 12 Similarly constructed fluorophore units lacking the calixarene cavities showed no fluorescence changes in the presence of this gas, thus suggesting the unprecedented NO host–guest complexation mechanism operating in our systems. 13 While unresponsive to other common gases, such as O 2 , CO, CO 2 , and water or hydrocarbons, these earlier molecular systems operate via a turn-off mechanism at relatively short wavelengths and with moderate sensitivity.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“… 8 , 9 Considering the importance of nitric oxide in a variety of biological processes, 10 we developed the fluorescent oxygen-depleted 5,5′-bicalixarene scaffolds 11 for reversible NO detection in solution. 12 Similarly constructed fluorophore units lacking the calixarene cavities showed no fluorescence changes in the presence of this gas, thus suggesting the unprecedented NO host–guest complexation mechanism operating in our systems. 13 While unresponsive to other common gases, such as O 2 , CO, CO 2 , and water or hydrocarbons, these earlier molecular systems operate via a turn-off mechanism at relatively short wavelengths and with moderate sensitivity.…”
mentioning
confidence: 83%
“…This is particularly true with regard to the detection of small gaseous compounds where no fluorescent probes have been reported despite the ability of such molecules to penetrate organic hosts, to the best of our knowledge . At the beginning of the century, Rathore et al reported NO gas capture by the colored oxidized calixarene scaffolds leading to a significant color change. , Considering the importance of nitric oxide in a variety of biological processes, we developed the fluorescent oxygen-depleted 5,5′-bicalixarene scaffolds for reversible NO detection in solution . Similarly constructed fluorophore units lacking the calixarene cavities showed no fluorescence changes in the presence of this gas, thus suggesting the unprecedented NO host–guest complexation mechanism operating in our systems .…”
mentioning
confidence: 99%
“…Thei ntermediate precursors and M were fully characterized by nuclear magnetic resonance (NMR), including 1 H, 13 C, Tw o-Dimensional Correlation Spectroscopy (2D-COSY), Nuclear Overhauser Effect Spectroscopy (2D-NOESY), high resolution Electrospray Ionization-Time of Flight (ESI-TOF) and Matrix-Assisted Laser Desorption/Ionization-Time of Flight (MALDI-TOF) mass spectrometers.T he covalent polymer (P)w as prepared by polymerization of M through efficient Glaser-Hay homocoupling in an O 2 atmosphere (Scheme S3). [13] Gel permeation chromatography (GPC) analyses gave an umber average molecular weight (M n )o f 36 kD aa nd ap olydispersity index (PDI) of 1.95 for P (Figure S37). In the MALDI-TOF mass spectrum of P (Figure 2), as eries of peaks with as pecific interval approximate 1525 Da could be observed, corresponding to the molecular weight of ar epeating unit.…”
Section: Synthesis and Characterization Of Metallo-helicoid (H)mentioning
confidence: 99%
“…CAs are a kind of macrocyclic hosts composed of phenolic units linked by methylene groups at meta-positions, forming a unique basket-like shape and a hollow hydrophobic cavity. [54] CAs with n phenol units were called calix[n]arenes (C[n]As), generally composed of n = 4, 5, 6 and 8. CAs have various conformations according to the number of incorporated phenolic units.…”
Section: Amphiphilic Cas For Drug Deliverymentioning
confidence: 99%